THE VARK LEARNING STYLE OF NURSING AND MIDWIFERY STUDENTS - Janno Sinaga; Rinco Siregar; Amila Amila; Rinawati Sembiring (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2015)
Introduction. VARK is very important to facilitate the development of nursing and midwifery students, helping translate theory into practice, and making what is learned in the classroom a reality. It is important to assess the learning style ofstudents to cater for differing learning needs. The aim of the study were: 1) to identify learning style nursing and midwifery students, and 2) the differences of learning style between nursing and midwifery students. Method. A descriptive crosssectional study was performed by using VARK questionnaire version 7.8. A total of 241 students including 125 nursing and 116 midwifery students were participated in this study that selected using stratifi ed random sampling techniques. Data analysis used Chi square test and One Way ANOVA (α=0.05). Result. The study showed that 61.7% and 67.8% nursing and midwifery students in the fi rst year; 70.8% and 63.3% in the second-year were used multimodal learning preferences, respectively. There was no signifi cantly differences learning preferences between the fi rst and the second-year as well as between nursing and midwifery students (p>0.05). Discussion. The nursing and midwifery students have varies on the learning preferences however the majority of the students used multimodal. Therefore, an active learning method was recommended. Keywords: Learning style, Nursing and midwifery students, VARK